El Inicio de la Formación en Angola: Percepciones de los Profesores de ISCED de Cabinda y Huambo - Helena Canhici; Carlinda Leite; Preciosa Fernandes (Universidade Federal de Rondônia, 2019)
This article analyses the perceptions of Higher Institutes of Educational Sciences (ISCED) teachers from Cabinda and Huambo, Angola, about the characteristics of the initial teacher training models followed in those institutions. These perceptions were collected through a questionnaire survey with close-end questions, on a Likert scale. The answers of the 107 teachers were analised by a simple statistic, with support of the SPSS program, and the discourses related to the open-end questions were interpreted by the content analysis technique. The results point to the fact that the models used are empowering future teachers to reflect on the social and educational problems of the country, although they need to be reorganized to respond to 21st century challenges. According to the teachers who answered the survey, it is important that the training integrates theoretical and practical components, promotes the development of pedagogical and scientific skills, and provides students, future teachers, contact with initiation activities for scientific research and university extension.